Peran Dinas Pemuda dan Olahraga DKI Jakarta dalam Revitalisasi Gelanggang Remaja di Jakarta Timur - Desy Fitriati Samputri; Gun Gun Gumilar; Hanny Purnamasari (Yayasan Literasi Sains Indonesia, 2025)
The revitalization of youth centers in East Jakarta has been hampered from 2019 to 2024. This study aims to analyze the role of the Jakarta Provincial Youth and Sports Agency (Dispora) in revitalizing the youth centers in East Jakarta. The study focuses on three dimensions of government roles according to Pitana and Gayatri's theory: motivator, facilitator, and dynamic agent. This study uses a qualitative descriptive approach with data collection techniques including in-depth interviews, field observations, and documentation. The results show that Dispora also motivates the community to participate in using youth centers as public spaces that support sports, social, and educational activities. As a facilitator, Dispora provides representative facilities and infrastructure and manages fees to support health facilities. As a dynamic agent, Dispora builds cross-sector collaboration, including local community involvement and joint monitoring with relevant institutions. Although the revitalization has shown significant achievements, several obstacles remain, such as delays in project implementation in several sub-districts. This study recommends increasing the effectiveness of coordination, mapping community needs, and conducting regular evaluations of youth center management so that the benefits of revitalization can be felt evenly.